Serving temperature effects on milk flavor, milk aftertaste, and volatile-compound quantification in nonfat and whole milk - L.L. Francis; S.H. Kong; Delores H. Chambers; I.J. Jeon (Kansas Agricultural Experiment Station Research Reports, 2004)
Many people seem to prefer to drink milk when it is cold. Research describing flavor and aftertaste of milk, and then correlating these traits with their chemical composition, has not previously been done. The objectives of this study were to describe milk flavor and aftertaste by using a descriptive sensory panel and to quantify the headspace volatiles of nonfat and whole milk as a function of serving temperature. Headspace volatile compounds of milk samples served at 40°F and 60°F were quantified by using solid-phase microextraction (SPME) analysis, with a 75-Î¼m Carboxen- PDMS fiber, sampling milk at 140oF for 30 minutes, and then analyzing by gas chromatography, flame ion detection (GCFID) for quantification. Descriptive-panel results indicated that serving temperature did not affect the milk flavor. Nonfat milk flavor and texture were rated to have greater sour aromatics, and to be slightly chalky, flat, and bitter, but less sweet, than whole milk. Characterization of milk aftertaste at 15 seconds after swallowing indicated that nonfat milk had very slight sour and cooked attributes. Characterization of milk aftertaste at 90 seconds after swallowing indicated that nonfat milk had very slight cooked attributes and was less sweet than whole milk. Serving temperature did not affect concentrations of volatile compounds, but nonfat milk had a greater concentration of hexanal and lesser (P<0.05) concentrations of benzaldehyde, ethyl caproate, heptanal, 2-heptanone, and nonanal than whole milk did. These data provide evidence that fat contributes to the "flavor" and aftertaste attributes of milk more than serving temperature does.; Dairy Day, 2004, Kansas State University, Manhattan, KS, 2004;
Keywords: Dairy Day; 2004; Kansas Agricultural Experiment Station contribution; no. 05-112-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 941; Dairy; Milk aftertaste; Milk flavor; GC Analysis